2020
DOI: 10.4315/0362-028x.jfp-19-084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cooking Methods and Tea Marinades on the Formation of Heterocyclic Amines and Benzo[a]pyrene in Grilled Drumsticks

Abstract: The effects of different grilling methods and tea marinades on the formation of heterocyclic amines (HCAs) and benzo[a]pyrene (BaP) in grilled chicken drumsticks were investigated. This study showed that both the grilling method and type of charcoal used in charcoal grilling had a significant effect on the formation of HCAs and BaP. The total content of HCAs and BaP detected in drumsticks was the lowest under electric roasting, at 7.25 and 0.04 ng/g, respectively; thus, the electric grill can be used as an alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…The formation of HAs depends on the heating temperature, heating time and cooking method. When chicken drumsticks were grilled at 230 °C for 27 min, many HAs, including IQ, Harman, Norharman, PHIP, MeIQx and AαC were detected ( Yao et al, 2020 ). However, only IQx was detected when drumsticks were deep-fat fried at 175 °C in sunflower oil for 8.5 min ( Haskaraca et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of HAs depends on the heating temperature, heating time and cooking method. When chicken drumsticks were grilled at 230 °C for 27 min, many HAs, including IQ, Harman, Norharman, PHIP, MeIQx and AαC were detected ( Yao et al, 2020 ). However, only IQx was detected when drumsticks were deep-fat fried at 175 °C in sunflower oil for 8.5 min ( Haskaraca et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some publications also have described the phenomenon of alleviating HAs emergence in meat products by different cooking methods. The HAs level of electric grilled drumsticks was considerably lower compared with that of gas-grilled ones ( Yao et al, 2020 ). The highest content of HAs was found in lamb patties cooked by stewing, followed by roasting, frying and pan-frying ( Guo et al, 2014 ).…”
Section: Introductionmentioning
confidence: 96%
“…Yao et al [107] analyzed the levels of BaP in grilled chicken drumsticks using electric and charcoal grilling. Prior to cooking, the samples were marinated with green and white tea.…”
Section: Meats and Meat Productsmentioning
confidence: 99%
“…More recently, with addition of 1% of green tea, oolong tea, or white tea extract, Yao et al. (2020) demonstrated that all the three tea extracts could inhibit the formation of HAAs including IQ, harman, norharman, PhIP, and AαC in wood charcoal‐grilled chicken (230°C/27 min), with the white tea extract showing the highest inhibitory effect (23%) compared to control (basic spice marinade), followed by oolong tea extract (18%) and green tea extract (16%). In addition, coffee consumption was reported to alleviate the DNA damage induced by oxidative stress and Trp‐P‐2, respectively, by 17 and 35% in human lymphocytes due to a 38% rise in superoxide dismutase level (Bichler et al., 2007).…”
Section: Inhibition Of Extracts Rich In Polyphenols On Haas Formationmentioning
confidence: 99%